Activation of guanylate cyclase by superoxide dismutase and hydroxyl radical: a physiological regulator of guanosine 3',5'-monophosphate formation. - Mittal, C K (1977)
Partially purified soluble rat liver guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2] was activated by superoxide dismutase (superoxide: superoxide oxidoreductase, EC 1.15.1.1). This activation was prevented with KCN or glutathione, inhibitors of superoxide dismutase. Guanylate cyclase preparations formed superoxide ion. Activation by superoxide dismutase was further enhanced by the addition of nitrate reductase. Although guanylate cyclase activity was much greater with Mn2+ than with Mg2+ as sole cation cofactor, activation with superoxide dismutase was not observed when Mn2+ was included in incubations. Catalase also decreased the activation induced with superoxide dismutase. Thus, activation required the formation of both superoxide ion and H2O2 in incubations. Activation of guanylate cyclase could not be achieved by the addition of H2O2 alone. Scavengers of hydroxyl radicals prevented the activation. It is proposed that superoxide ion and hydrogen peroxide can lead to the formation of hydroxyl radicals that activate guanylate cyclase. This mechanism of activation can explain numerous observations of altered guanylate cyclase activity and cyclic GMP accumulation in tissues with oxidizing and reducing agents. This mechanism will also permit physiological regulation of guanylate cyclase and cyclic GMP formation when there is altered redox or free radical formation in tissues in response to hormones, other agents, and processes.